2021
DOI: 10.1186/s12877-021-02191-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease and cumulative incidence of cognitive impairment in the Health and Retirement Study

Abstract: Background We sought to examine whether people with a diagnosis of cardiovascular disease (CVD) experienced a greater incidence of subsequent cognitive impairment (CI) compared to people without CVD, as suggested by prior studies, using a large longitudinal cohort. Methods We employed Health and Retirement Study (HRS) data collected biennially from 1998 to 2014 in 1305 U.S. adults age ≥ 65 newly diagnosed with CVD vs. 2610 age- and gender-matched c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Other than CANHEART, specific CVD risk models were associated with a lower risk for dementia or cognitive decline ( Covello et al, 2021 ; Jeon et al, 2021 ; Speh et al, 2021 ). CVD risk models from multiethnic cohorts were proven to predict dementia or cognitive decline in diverse race populations, such as White, H/L, Black, or Asian.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than CANHEART, specific CVD risk models were associated with a lower risk for dementia or cognitive decline ( Covello et al, 2021 ; Jeon et al, 2021 ; Speh et al, 2021 ). CVD risk models from multiethnic cohorts were proven to predict dementia or cognitive decline in diverse race populations, such as White, H/L, Black, or Asian.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence demonstrates that heart and brain health are inextricably linked ( Zhao et al, 2023 ). Patients diagnosed with cardiovascular disease (CVD) usually had poorer cognition than those without CVD ( Covello et al, 2021 ). According to the most recent descriptions of novel pathological reasons, mixed dementia (Alzheimer’s disease and cerebrovascular injuries) is more common among the oldest seniors (those over 90 years old; Livingston et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective cohort study of predominantly younger adults found CVD diagnosis increased the risk of dementia by 17% 4 . However, despite previous reports that incident CVD accelerated cognitive decline, a large recent study of older adults (mean 73 years) found no increased risk of cognitive impairment among participants with CVD compared with no CVD 5 …”
Section: Introductionmentioning
confidence: 93%
“…4 However, despite previous reports that incident CVD accelerated cognitive decline, a large recent study of older adults (mean 73 years) found no increased risk of cognitive impairment among participants with CVD compared with no CVD. 5 Furthermore, the majority of past studies examined individual CVD events. There is good evidence that stroke, which causes direct end organ damage, is associated with an increased risk of cognitive decline and dementia [6][7][8][9] ; however, fewer studies have investigated the association with other CVDs.…”
Section: Introductionmentioning
confidence: 99%